Probabilistic durability prediction of existing building elements - Kliukas, Romualdas; Kudzys, Antanas (Journal of Civil Engineering and Management, 2004)
An effect of service and proof actions on probabilistic reliability (serviceability, safety and durability) of building elements (components and members) of existing enclosure and bearing structures is under consideration. Time‐dependent models for reliability assessment of elements under sustained variable and multicycle actions are presented. Revised reliability indices of existing elements exposed to service permanent and variable actions are discussed. It is recommended to assess the long‐term reliability index of elements taking into account the effect of latent defects. Truncated probability distributions of physical‐mechanical resistances of elements and an effect of their latent defects on reliability index assessment are taken into account. Methodological peculiarities of durability prediction of elements and avoiding unfounded premature repairs or replacements are analysed. The applied illustration of the presented method on the probabilistic reliability prediction of deteriorating concrete covers is demonstrated. First Published Online: 14 Oct 2010